Compound Heterozygous Hemoglobin SD Disease Presenting as Sickle Cell Crisis in Pregnancy - , Rakhi; Rohilla, Minakshi; Malhotra, Pankaj; Das, Reena; Jain, Vanita; Prasad, GRV; Kalra, Jasvinder (Journal of Women's Reproductive Health, 2016)
A case report of compound heterozygous hemoglobin SD disease presenting as sickle crisis during pregnancy. The discussion covers transfusion, pain control, and peripartum care.
Keywords: Compound Heterozygous; Hemoglobin SD Disease; Sickle Cell Crisis; Pregnancy; Transfusion